The woman, who didn’t exist. The female identity in the novel of Ingeborg Bachmann Der Fall Franza - Bogdańska, Patrycja (Acta Universitatis Lodziensis. Folia Germanica, 2018)
When discussing the literary output of Ingeborg Bachmann, the role of the female identity, of the fear and of the feeling of inferiority cannot be ignored. It was an inseparable element of her creation. Bachmann became an icon of the feminist movement in the 80s, particularly because of the series of books Todesarten, that she was working on from 1962/1963 up to her death. Only a few novels appeared in her lifetime: Malina (1971), a tom of short stories Simultan (1972) and a prose Ein Ort für Zufälle (1964). One of the novels of this series, Der Fall Franza shows the woman as a victim and the man as a sadist. It is a critical voice to the ruling social order. There is the a question, what was the role of the woman in the patriarchal world?